2015
DOI: 10.1371/journal.pgen.1005142
|View full text |Cite
|
Sign up to set email alerts
|

Methylation-Sensitive Expression of a DNA Demethylase Gene Serves As an Epigenetic Rheostat

Abstract: Genomes must balance active suppression of transposable elements (TEs) with the need to maintain gene expression. In Arabidopsis, euchromatic TEs are targeted by RNA-directed DNA methylation (RdDM). Conversely, active DNA demethylation prevents accumulation of methylation at genes proximal to these TEs. It is unknown how a cellular balance between methylation and demethylation activities is achieved. Here we show that both RdDM and DNA demethylation are highly active at a TE proximal to the major DNA demethyla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(146 citation statements)
references
References 61 publications
(93 reference statements)
7
138
1
Order By: Relevance
“…In this study, we identified 4580 hypo DMRs and 2348 hyper DMRs in nrpd1 (Pol IV largest subunit) mutant compared to wild type plants; the large number of hypo DMRs in the Pol IV mutant is consistent with the role of Pol IV in DNA methylation. The more than 2000 hyper DMRs in Pol IV may be related to reduced expression level of ROS1 in nrpd1 mutant 23,24 (see below).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identified 4580 hypo DMRs and 2348 hyper DMRs in nrpd1 (Pol IV largest subunit) mutant compared to wild type plants; the large number of hypo DMRs in the Pol IV mutant is consistent with the role of Pol IV in DNA methylation. The more than 2000 hyper DMRs in Pol IV may be related to reduced expression level of ROS1 in nrpd1 mutant 23,24 (see below).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, studies revealed that the expression of ROS1 is finely tuned by RdDM and DNA demethylation pathways 23,24 , although the genome-wide interaction between ROS1-mediated DNA demethylation and RdDM has not been investigated. In this study, we generated and analyzed the DNA methylomes of ros1 mutants in both Col-0 and C24 ecotypes of Arabidopsis, and characterized ROS1 target loci in these two genetic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…This near-gene TE is targeted both by RdDM to add DNA methylation and the ROS1 protein to remove DNA methylation. The methylation at this promoter-proximal TE stimulates expression of ROS1, and the ROS1 enzyme then acts to demethylate this TE (as well as many others), thereby affecting its own expression and acting as an "epigenetic rheostat" or "methylstat" controlling the rate of demethylation from genic targets ( Figure 3B) (Lei et al, 2015;Williams et al, 2015). This mechanism thus explains why ROS1 protein accumulation is reduced in several RdDM mutants (Penterman et al, 2007a).…”
Section: Tes Near Genesmentioning
confidence: 98%
“…Unlike most loci, ROS1 expression increases when methylated and, conversely, decreases when unmethylated. ROS1 functions to remove DNA methylation, and its expression regulation represents an elegant mechanism to maintain DNA methylation homeostasis (Lei et al, 2015;Williams et al, 2015). This autoregulation mechanism differs from that of DCL4, which does not play a direct role in the DNA methylation pathway.…”
Section: Feedback Regulation and Epigenetic Control Of Rna Silencing mentioning
confidence: 99%